Replication Study of the Milwaukee Inventory for Subtypes of Trichotillomania–Adult Version in a Clinically Characterized Sample. (July 2015) - Keuthen, Nancy J.; Tung, Esther S.; Woods, Douglas W.; Franklin, Martin E.; Altenburger, Erin M.; Pauls, David L.; Flessner, Christopher A.
In the present study, we evaluated the Milwaukee Inventory for Subtypes of Trichotillomania–Adult Version (MIST-A) in a replication sample of clinically characterized hair pullers using exploratory factor analysis (EFA; N = 193). EFA eigenvalues and visual inspection of our scree plot revealed a two-factor solution. Factor structure coefficients and internal consistencies suggested a 13-item scale with an 8-item "Intention" scale and a 5-item "Emotion" scale. Both scales displayed good construct and discriminant validity. These findings indicate the need for a revised scale that provides a more refined assessment of pulling phenomenology that can facilitate future treatment advances.